Factors affecting strategic plan execution process in public healthcare - Shopati, Abner Kukeyinge; Mitonga, Kabwebwe Honore; Aipinge, Lydia Penomuntu (International Journal Of Community Medicine And Public Health, 2018)
Background: The managers of healthcare Organization must confront numerous impediments and curbs issues that significantly contribute to the trial of quantifying, testing, and meritoriously use execution strategies that work in healthcare setting. The aim of the research is to explore and confirm the active factors of failure for the strategic plan execution in state healthcare in Namibia. Methods: The research utilized quantitative approach, a survey design and questionnaire was employed to collect data. The study used Gaskin’s CFA/SEM procedure and applies the SPSS 23 AMOS plugins, Pattern Matrix Model Builder” (PMMB), “Master Validity” (MV), “Model fit measures” (MFM) to validate and determine the interrelationships between variables. Results: Studying literature, 17 variables were recognized and Implementation failure factors (IFF) model with two key factors was established, IFF for strategic plan formulation and IFF for strategic plan implementation. The factors were then reduced using exploratory factor analysis which is evaluated using Principal Axis Factoring with Direct Oblimin rotation. Structural modelling equation (SEM) approach was used, variables were assembled into 4 factors dimension measurement. This model, recognized four factors, contextual dimensions (0.34), content dimensions (0.31), operational dimensions (0.23) and Structural dimensions (0.04) are the main reasons for failure of strategic plan implementation in public health care in Namibia. Conclusions: The research shows that exploring and confirming implementation failure factors in public healthcare organization in developing countries, it will be plausible to consider IFFs for strategic plan formulation and IFFs for strategic plan implementation. Structural equation modelling/CFA has been run to prove the validity of basic IFFs in this research.